Social Security Financing: Facts, Fantasies, Foibles, and Follies - Clark, Robert L (American Economic Review, 2004)
Reforming Social Security to restore its financial balance is one of the most important public policy issues of the 21st century. Reform is essential whether one favors maintaining the basic structure of the current system or transforming this retirement program to include individual accounts. The needed national debate on Social Security must be based on the best, unbiased measures of the financial status of the program and on appropriate economic research. Unfortunately, projections, data, and research are often misused in reform debates. Even some “experts” are often uninformed about various aspects of the current and future financial status of Social Security. This paper highlights misconceptions and focuses on the facts of Social Security financing.